Efficacy Of Dry Needling, Intramuscular Dry Needling Stimulation And Coventional Treatment Over Quadratus Lumborum Amoung Low Back Pain Patients - Edwin Raj, S. Gerald; Ramalingam, Vinodhkumar; Shaju, M.K. Franklin (Journal of Neonatal Surgery, 2025)
Purpose: Around one quarter of persons experience chronic pain, and on average, the incidence of low back pain (LBP) can reach eighty-four percent LBP is characterized by lower back pain or discomfort and a reduction in flexion to the sides range of motion. Comparing the effectiveness of dry needling, lumborum muscle intramuscular dry needling stimulation (IMDNS), and conventional treatment (DN) in low back pain patients' distress, postural sway, and impairment was the goal of the study. Methods And Outcomes: 51 participants who met the study's inclusion criteria and had low back pain with lumborum muscle pain between the ages of 30 and 45 participated in a randomized control trial. Participants will be divided into three groups at random (1:1), and each group will receive three sessions per week for three weeks. Group A will receive IMDNS, Group B will receive DN, Group C will receive an IFT, and each of the three groups will receive a quadrat lumborum stretch. The outcome metrics consist of Functional disability, postural sway, and pain were evaluated at baseline (pre-intervention) and follow-up (post-intervention) using the Oswestry Disability Index (ODI), Lord's sway meter, and Numerical Pain Rating Scale, respectively. A significance level of p less than 0.05 was established for the data. Results: In three groups (A, B, and C), the study examined postural sway, disability, and pain in people with low back pain. Tukey's Post Hoc test and One-Way ANOVA were used to examine the data. The study discovered notable variations in back pain patients' postural sway, discomfort, and impairment. According to the findings, IMDN is a better course of treatment for people with low back pain. The null hypothesis is thus disproved. Disussion And Conclusion: According to earlier research, mechanical low back pain can be effectively treated with intramuscular dry needling, dry needling, and IFT combined with QL stretching. We were confident that the evidence-based treatment for mechanical low back pain employed in this study would result in notable improvements in functional impairment, postural sway, and pain. Intramuscular dry needling is more successful among the three groups.